Early life-stage thermal resilience is determined by climate-linked regulatory variation - Joaquin C. B. Nunez; Sumaetee Tangwancharoen; Kylie M. Finnegan; Eliza M. Bufferd; Olin C. King; Luke A. Proud; Brent L. Lockwood (Proceedings of the National Academy of Sciences, 2026)
The ecological context of developmental physiology remains largely unexplored. We previously showed that thermal selection primarily targets early embryos in Drosophila melanogaster . Here, we used advanced introgression and pooled whole-genome resequencing to map the genomic basis of enhanced embryonic heat tolerance in a neotropical line of D. melanogaster . We identified two loci on chromosomes 2R and X that were consistently targeted by 16 generations of thermal selection across six replicate introgressions. Global population comparisons revealed that two SNPs in these genomic regions exhibit clinal and seasonal patterns linked to environmental variability in average precipitation and temperature variance across space and time. The two SNPs lie in putative regulatory regions of the genes SP70 and sog , where allelic variation in gene expression correlates with heat tolerance. Using the Drosophila Genetic Reference Panel, we confirmed that tropical alleles at these loci increase embryonic heat tolerance and interact epistatically, demonstrating the genotype-to-phenotype link in an independent set of diverse genetic backgrounds. Overall, our study extends previous work in developmental genetics by showcasing developmental regulatory variants that appear to be under natural selection.